Effect of Coptidis Rhizoma on gastrointestinal system before and after processing with wine based on gut microbiota and short chain fatty acids - Tian, Rui; Wang, Wen-Xiao; Bai, Ya-Ya; Tang, Yu-Ping; Zhang, Qiao; Yue, Shi-Jun (Frontiers in Pharmacology, 2024)
Coptis deltoidea C.Y. Cheng et Hsiao (CD), commonly used in heat-toxin congestion and excessiveness. However, CD needs to be processed with wine for alleviating the bitter and cold of CD, meanwhile, reducing the gastrointestinal damage. The research assessed the discrepant effects of CD on gastrointestinal system before and after processing with wine, and explore the potential mechanisms.The ingredients in CD and CD processed with wine (PCD) were performed on Ultra Performance Liquid Chromatography Mass Spectrometry (UPLC-MS). The mice were treated with CD and PCD once a day for six weeks (0.65 and 2.6 g/kg, i.g.).The pathological changes of gastrointestinal tract were evaluated, and the serum inflammatory factors and Nuclear Factor kappa-light-chain-enhancer of activated B cells (NF-κB) RelA (p65) protein of tissues were determined. The short chain fatty acids (SCFAs) of feces were analyzed by UPLC-MS, the gut microbiota (GM) changes were performed on 16S rRNA sequencing.Results: Ingredients analysis declared that the alkaloids, flavonoids, phenylpropanoid compounds were the main metabolites in CD and PCD. CD reduced body weight and food intake, and the effect of CD on fecal water content increased first and then decreased with the prolongation of administration time, while its effect on intestinal transport time was exactly the opposite, reduced the SCFAs contents of feces. CD caused different degree of damage to the gastrointestinal tract, and the effect on the small intestine and colon was more obvious, which increased the expression of NF-κB p65 and elevated the inflammatory factors levels. PCD were weaker than that of CD.In addition, CD and PCD can change the composition of GM, and reduced the levels of Lactobacillus, Allobaculum, Ruminococcus, and norank_f_S24-7, increased the levels of Akkermansia, Dorea, Bacteroides, and Blautia at the genus level. However, PCD induced a milder effect of GM dysregulation than that of CD.CD can cause damage to the gastrointestinal tract, which may be related to the GM disorders, SCFAs changes-mediated by GM, abnormal NF-κB p65 expression and increased inflammatory factors levels, interestingly, PCD had a lower effect than CD, which may be related to the differences in the types and contents of ingredients in CD after processing.